ANALYSIS OF THE PROBLEMS OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS - Basysyar, Andi Haura Rafiqah; Anggraeni, Warda; Rahmah, Sri (Al-Mubin, 2025)
This study aims to find out the problems that occur in the implementation of the independent curriculum in religious subjects at SDN 22 Jeppe'e, Bone Regency. The type of research is qualitative descriptive research. Data collection techniques are in the form of interviews and literature reviews. The data analysis technique used is qualitative descriptive analysis. The results of the study show that the implementation of the Independent Curriculum in Islamic Religious Education subjects at the elementary school level faces several problems that are obstacles in the implementation of maximum learning